Low-cost simulation model for ultrasound-guided punch biopsy and puncture: Construction manual and photo examples - Lüdke, Theresa; Paliege, Alexander; Kluge, Anne; Olesch, Falk-Tony; Hilger, Gregor; Beleites, Thomas; Kemper, Max (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Purpose Ultrasound-guided puncture and punch biopsy pose a particular challenge in ultrasound examination training. These techniques should be learned and performed several times using a simulation model that is as realistic as possible before being applied to patients. While the use of agar-agar-based models is extensively documented in the literature, there is a discernible gap in publications specifically addressing their use in punch biopsy and puncture. The aim was to develop a cost-effective model for the simulation of ultrasound-guided interventions.Materials and Methods The developed simulation model is based on the vegetable gelatine agar-agar. The agar-agar powder is boiled in water and colored. Various objects are added to the mass. Blueberries, olives, tomatoes, and cornichons imitate solid structures. Liquid-filled balloons are used to simulate cystic structures. Adding stones can make the exercises more difficult due to hyperechoic reflexes with distal shadowing.Results With the model, ultrasound-guided puncture and punch biopsies could be successfully simulated, and ultrasound images can be generated for this purpose. The cost of a single model is about 2 euros. Production takes less than 2 hours, including cooling. The pure processing time is 30 minutes. The durability of the models is limited by mold, which occurs after 5 days when stored at room temperature and after 5 weeks in the refrigerator.Conclusion It was shown that it is possible to produce an inexpensive agar-agar-based ultrasound model in a short time and with easily available ingredients to learn ultrasound-guided puncture and punch biopsies.
Keywords: Punch biopsy; Puncture; Simulation model; Ultrasound training; Head and neck